Psychological, addictive, and health behavior implications of the COVID-19 pandemic (2020)
The public health impact of COVID-19 on psychological symptoms and disorders, addiction, and health behavior is substantial and ongoing. The aim of this invited article in Behaviour Research and Therapy is to offer a conceptual essay that discusses the potential psychological, addictive, and health behavior correlates/issues related to the COVID-19 pandemic from a behavioral science perspective. In the first section, we describe the COVID-19 implications for mental health focusing on anxiety/stress and mood disturbance, obsessive compulsive symptoms and disorders, and posttraumatic stress. In the second section, we focus on addictive behaviors, including tobacco (combustible and electronic), alcohol use and misuse, and cannabis. In the third section, we spotlight health behavior and chronic illness by discussing the role of sleep, chronic illness using the example of HIV/AIDS as an illustrative model, and physical activity. In the final section, we highlight sociocultural factors (e.g., race/ethnicity, economic adversity), developmental considerations, and the role of individual difference factors (e.g., transdiagnostic factors) for psychological, addictive, and health behavior and chronic illness. We conclude by offering an integrative COVID-19 stress-based model that could be used to guide research focused on the stress-related burden of the pandemic.